2004
DOI: 10.1002/adsc.200303182
|View full text |Cite
|
Sign up to set email alerts
|

High‐Pressure 31P{1H} NMR Studies of RhH(CO)(TPPTS)3 in the Presence of Methylated Cyclodextrins: New Light on Rhodium‐Catalyzed Hydroformylation Reaction Assisted by Cyclodextrins

Abstract: The effect of methylated cyclodextrins on the RhH(CO)(TPPTS) 3 complex in hydroformylation conditions [50 atm of CO/H 2 (1/1) and 80 8C] has been investigated by high-pressure 31 P{ 1 H} NMR spectroscopy. In the presence of methylated b-cyclodextrin, the equilibria between the rhodium species lie in favor of phosphine low-coordinated rhodium species. The formation of a stable inclusion complex between this cyclodextrin and the trisulfonated triphenylphosphine ligand (TPPTS) was found to be the key to understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 46 publications
(20 reference statements)
0
46
1
Order By: Relevance
“…In particular, the aldehydes selectivity and the linear to branched ratio (l/b ratio) of aldehyde products are indicative of the nature of the catalytic species and of interactions between the CD and the phosphane, respectively. [6] Indeed, we have demonstrated that the l/b ratio decrease observed in the presence of RAME-b-CD (1.8 vs. 2.8 without CD) was due to trapping of the phosphane ligand by CD and it is suspected that the high aldehydes selectivity (97% vs. 59% without CD) is due to an interaction between the CD and the catalytic rhodium species during coordination of the olefin on the metal center.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In particular, the aldehydes selectivity and the linear to branched ratio (l/b ratio) of aldehyde products are indicative of the nature of the catalytic species and of interactions between the CD and the phosphane, respectively. [6] Indeed, we have demonstrated that the l/b ratio decrease observed in the presence of RAME-b-CD (1.8 vs. 2.8 without CD) was due to trapping of the phosphane ligand by CD and it is suspected that the high aldehydes selectivity (97% vs. 59% without CD) is due to an interaction between the CD and the catalytic rhodium species during coordination of the olefin on the metal center.…”
Section: Resultsmentioning
confidence: 96%
“…[10] Second, as it has been demonstrated that inclusions between RAME-b-CD and phosphanes greatly affected the performance of catalytic systems, [6,7] an NMR study has been performed to provide information about the ability of KSPDM-b-CD to interact with hydrosoluble phosphane ligands. Two phosphanes widely used in aqueous organometallic catalysis have been chosen for this study: the sodium salt of the meta-substituted trisulfonated triphenylphosphine (TPPTS) and the sodium salt of the meta-substituted monosulfonated triphenylphosphine (TPPMS).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] The formation of such inclusion complexes induces a decrease in the linear to branched aldehyde ratio during the rhodium-catalyzed hydroformylation reaction. [7] In fact, the Rame-b-CD is able to dissociate TPPTS from the rhodium species and leads to the formation of low-coordinated phosphane species responsible for this decrease in regioselectivity. In addition, it has been shown that the ability of Rame-b-CD to bind to the TPPTS ligand can contribute to decrease the reaction rates.…”
Section: Introductionmentioning
confidence: 99%
“…[6] In this context, it was of great interest to evaluate in a cyclodextrin-based hydrofomylation process the behavior of rhodium complexes associated to the highly water-soluble ligand m-TPPTC [tris(m-carboxyphenyl) phosphane trilithium salt] (Scheme 1), a carboxylated analogue of the sulfonated TPPTS ligand.…”
Section: Introductionmentioning
confidence: 99%